Prime Minister’s Decree No. 3004 of the Year 2024 = قرار رئيس مجلس الوزراء رقم 3004 لسنة 2024 بشأن توفيق أوضاع اقامة الأجانب - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic